(untitled) (Cambridge, 1987)
Testing economic propositions in laboratory experiments has proven a very fruitful research endeavor in recent years. This volume brings together the major contributors to experimental economics. The papers present their views on the way experiments should be done, on the power and limitations of the techniques, and on the areas in which experimentation could contribute substantially to our understanding of economic behavior. This book distills the main lessons from great experience in experimental work. It will be essential reading for all who wish to follow experimental work or who wish to do such work themselves
Keywords: Economics; Experiments,Kinh tế học; Thử nghiệm